Frequency of pediatric migraine with aura in a clinic‐based sample. Issue 1 (21st December 2015) - Genizi, Jacob; Khourieh Matar, Amal; Zelnik, Nathanel; Schertz, Mitchell; Srugo, Isaac
Abstract : Objective: To assess the prevalence and risk factors for pediatric migraine with aura (MWA) among patients presenting to pediatric neurology clinics. Background: Headache is a common complaint among children, and the prevalence of migraine is about 8%. Up to one third of adults with migraine report experiencing aura; however, the exact percentage in children is unknown. Methods: Medical records of children presenting with headache to three pediatric neurology clinics in Haifa in the last 5 years were retrospectively reviewed. Inclusion criteria were a diagnosis of migraine headache at 5‐18 years of age. Results: Of 260 children (140 female) who had migraine, 26.2% experienced aura. MWA was more common among females compared to males (32.6% vs 18.9%, P < .01) and among older children (OR: 2.50, 95% CI: 1.20‐5.20; P < .01). Among those who experienced aura, visual aura was more common in females than males (66.7% vs 33.3%, P < .04). Family history of migraine was strongly related to MWA ( P < .02): the odds of MWA were 2.46 times greater in children who had a family history of migraine. (OR: 2.46, 95% CI: 1.08‐5.62; P < .03). Conclusions: MWA is as common in children as in adults. Aura is more common in older children. Children who have MWA are more likely to have a family history of migraine.